The development and validation of the Chinese safety climate scale using the item-response theory approach - Lyu, Xiaokang; Zhao, Binlin; Yang, Tingting; Zhao, Li (Frontiers in Psychology, 2023)
To develop a valid and practical tool to measure the safety climate in China, and further raise awareness of it in Chinese industries, we developed the Chinese safety climate scale (including two subscales at the levels of organization and group separately) based on the work of Huang et al. (2017). A descriptive survey with the convenience sampling method was conducted in Shanghai Disney Resort, China. A sample of 1,570 employees was involved in the final data analyses. The item response theory (IRT) analyses with graded response models were conducted using. The unidimensionality and local independence assumption were held. The Cronbach's α of organization- and group- level safety climate subscale was 0.912 and 0.937, respectively. The confirmatory factor analysis (CFA) showed good model fit for a one-factor model of the organization-level safety climate subscale, 2(df = 20) = 129.158, p < 0.001, CFI = 0.994, TLI = 0.992, NFI = 0.993, IFI = 0.994, RMSEA = 0.059, 90% CI = [0.050, 0.069], and SRMR = 0.048. A one-factor model also fits well for the group-level safety climate subscale, 2(df = 44) = 219.727, p < 0.001, CFI = 0.996, TLI = 0.9925 NFI = 0.995, IFI = 0.996, RMSEA = 0.050, 90% CI = [0.044, 0.057], and SRMR = 0.046. Discrimination and difficulty parameters showed that all items effectively spanned the range of the latent trait and could successfully separate participants at different safety climate levels. Items in the organization-level and group-level Chinese safety climate subscales had significantly different discrimination parameters, fitted well with the models, and had a substantive relationship with the latent traits. The Chinese safety climate scale was reliable and valid overall. They can facilitate the research and survey regarding the safety climate in China.